Mitochondrial DNA suggests the existence of two distinct species in Moluccas and New Guinea within Nyctimystes infrafrenatus (Günther, 1867) - Taufan Nurzaman Sulaeman; AMIR HAMIDY; ACHMAD FARAJALLAH; ANTOINE FOUQUET; AWAL RIYANTO; EVY ARIDA; MULYADI Mulyadi; WAHYU TRILAKSONO; MISBAHUL MUNIR (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sulaeman TN, Hamidy A, Farajallah A, Fouquet A, Riyanto A, Arida E, Mulyadi, Trilaksono W, Munir M. 2021. Mitochondrial DNA suggests the existence of two distinct species in Moluccas and New Guinea within Nyctimystes infrafrenatus (Günther, 1867). Biodiversitas 22: 3287-3297. Nyctimystes infrafrenatus is a widespread frog species distributed across northern Australia, New Guinea, Bismarck archipelago and in the eastern part of Indonesian archipelago. The species thus encompasses two biogeographic regions, Papua and Wallacea. We evaluated the phylogenetic relationships among the populations from Papua and Moluccas based on two mitochondrial loci (16S rRNA and Cytochrome Oxidase Subunit I). Two major subclades are recovered within Nyctimystes infrafrenatus with subclade A being represented by populations from New Guinea and northern Australia and subclade B by Moluccan populations (Halmahera and Tidore). Genetic distances (2.3-4.2% in 16S rRNA) between these subclades suggest they could belong to distinct species. Since New Guinea populations correspond to the nominal species and that Nyctimystes tennuigranulatus (Boettger 1895), currently considered as a junior synonym of Nyctimystes infrafrenatus, is available for the northern Moluccan populations, we proposed to remove this taxon from synonymy. However, samples used in this study come from northern Moluccas, further studies including samples from Ambon (where another synonym was described i.e. Calamita dolichopsis) is needed to determine the taxonomic status of the southern Moluccan population whether they are conspecific with northern Moluccan population or not.